Understanding consumer behavior in Kuching’s black market gambling: the psychological, economic, and regulatory impacts of illicit gambling markets / Rudy Ujang - Ujang, Rudy (Faculty of Business and Management ; UiTM Press, 2024)
This study investigates the social, psychological, economic, and regulatory elements that influence Kuching, Sarawak, residents' involvement in illegal gaming. Using a non-probability purposive sampling technique and a structured questionnaire, data were gathered from 366 respondents. To get a wide variety of respondents, the survey was administered online. Key findings show that social influence, financial difficulty, and psychological pressure all strongly influence gambling behavior, with accessibility to illicit internet gambling platforms appearing as a key contributing factor. The study also shows that the problem is made worse by lax regulatory enforcement, which lets players bet with little concern about potential legal consequences. Regression analysis shows that both psychological health and economic stability are significantly harmed by consumer involvement in black market gaming. To address the root reasons of gambling habits, the study suggests community-based initiatives, economic interventions, the creation of legal alternatives, and more stringent regulation and oversight of online gaming platforms.